New Target for Precision Medicine Treatment of Giant-Cell Tumor of Bone: Sunitinib Is Effective in the Treatment of Neoplastic Stromal Cells with Activated PDGFRβ Signaling - Mahdal, Michal; Neradil, Jakub; Mudry, Peter; Paukovcekova, Silvia; Staniczkova Zambo, Iva; Urban, Jiri; Macsek, Peter; Pazourek, Lukas; Tomas, Tomas; Veselska, Renata (Cancers, 2021)
Giant-cell tumor of bone (GCTB) is an intermediate type of primary bone tumor characterized by locally aggressive growth with metastatic potential. The aim of this study was to identify new druggable targets among the cell signaling molecules involved in GCTB tumorigenesis. Profiles of activated signaling proteins in fresh-frozen tumor samples and tumor-derived cell lines were determined using phosphoprotein arrays. Analysis of the obtained data revealed epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor beta (PDGFRβ) as potential targets, but only the PDGFR inhibitor sunitinib caused a considerable decrease in stromal cell viability in vitro. Furthermore, in the case of a 17-year-old patient suffering from GCTB, we showed that the addition of sunitinib to the standard treatment of GCTB with the monoclonal antibody denosumab resulted in the complete depletion of multinucleated giant cells and mononuclear stromal cells in the tumor tissue. To summarize, the obtained data showed that a specific receptor tyrosine kinase (RTK) signaling pattern is activated in GCTB cells and plays an important role in the regulation of cell proliferation. Thus, activated RTKs and their downstream signaling pathways represent useful targets for precision treatment with low-molecular-weight inhibitors or with other types of modern biological therapy.